2018
DOI: 10.5194/tc-2018-211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathways of ice-wedge degradation in polygonal tundra under different hydrological conditions

Abstract: Abstract. Ice-wedge polygons are common features of lowland tundra in the continuous permafrost zone and prone to rapid degradation through melting of ground ice. There are many inter-related processes involved in ice-wedge thermokarst and it is a major challenge to quantify their influence on the stability of the permafrost underlying the landscape. In this study we used a numerical modelling approach to investigate the degradation of ice-wedges with a focus on the influence of hydrological conditions. Our st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…4b and c) and mimic the observed conditions more closely (see Boike et al, 2013, 2018. The simulated maximum snow depths in 2008 compare well with observations for both RIM (0.23 m compared to 0.16 m) and the centers (0.39 m compared to 0.46 m), although the observa- tions show a considerable spread (see Nitzbon et al, 2018). This was partly achieved by applying a scaling factor for precipitation (P scale ) of 0.6 ( Table 2).…”
Section: Samoylov Island Northern Siberiasupporting
confidence: 74%
See 4 more Smart Citations
“…4b and c) and mimic the observed conditions more closely (see Boike et al, 2013, 2018. The simulated maximum snow depths in 2008 compare well with observations for both RIM (0.23 m compared to 0.16 m) and the centers (0.39 m compared to 0.46 m), although the observa- tions show a considerable spread (see Nitzbon et al, 2018). This was partly achieved by applying a scaling factor for precipitation (P scale ) of 0.6 ( Table 2).…”
Section: Samoylov Island Northern Siberiasupporting
confidence: 74%
“…1b;Boike et al, 2013Boike et al, , 2018). All degradation stages described by Liljedahl et al (2016) can be found here, from non-degraded LCPs to HCPs with connected troughs (see Nitzbon et al, 2018). Between 1997 and 2017, the mean annual air temperature at the island was approximately −12.3 • C, with an annual liquid precipitation of 169 mm and mean end-of-winter snow depth of 0.3 m (Boike et al, 2018).…”
Section: Samoylov Island Northern Siberiamentioning
confidence: 90%
See 3 more Smart Citations